(3MGTjI GdSjO GdTQja Ydi TQM GdbWH GdQGRj Ydi GdQSGdI GdTeSjI ddbRhjfjs - (3GdLQLGfj, Ydj Hf eMeO Hf Ydj,, GdeYQha HGdTQja GdLQLGfj J (B816 (3g`s ((3bUHI GOhfjs)
(3ChdgG (B:s
(3HYO GdHSedI ; bhdg hQJHJg Ydi ebOeI hKdGK ebGdGJ hNGJeI Cbhd gcPG hLO YHGQI GdeJf aj cKjQ ef GdfSN hGdUhGH Cf daX KdGK ggfG RjGOI hbYJ SghGs
(3BNQgG (B:s
(3ef GdeHGOF GdJUOjb adG jchf LRA CjVG Ydi MOI Hd efOQLG aj GdeHGOF GdJUOjbjI hGddg CYdes
(3efbhdI ef fSNI GdeDda GdeDQNI H (B753 (3g` (B- (3aj Chdg ebOeI efShNI SfI (B1197 (3g` hCNQi SfI (B1099 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5/ 7s
(3eYLe GdeDdajf (B2 / 515s
(3cTa GdXfhf (B2 / 1063s
(3gOjI GdYGQajf (B1/ 728s
Keywords: (3GdadSaI hGdefWbs